1982
DOI: 10.1002/aja.1001650304
|View full text |Cite
|
Sign up to set email alerts
|

Monoamines in the early chick embryo: Demonstration of serotonin synthesis and the regional distribution of serotonin‐concentrating cells during morphogenesis

Abstract: Monoamine compounds, such as serotonin (5-HT), have been previously suggested to regulate the early development of the chick embryo. Possible roles for 5-HT in chick morphogenesis were investigated further by examining the distribution of sites that concentrate 5-HT as well as the ability of embryos to synthesize 5-HT during this period. Following the in vitro incubation of chick embryos with 5-HT, cells accumulating 5-HT were localized by the formaldehyde-induced fluorescence (FIF) technique; these sites of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…1D-N K, M, N). Catecholamine fluorescence, which is indicative of catecholamine uptake or synthesis, has been described previously in the notochord and somite by Kirby and Gilmore [1972], Strudel et al [1977], Lauder et al [1980], Newgreen et al [1981], and Wallace [1982]. Our current observations thus confirm their data.…”
Section: Net Immunoreactivity In the E35 Quail Embryosupporting
confidence: 92%
“…1D-N K, M, N). Catecholamine fluorescence, which is indicative of catecholamine uptake or synthesis, has been described previously in the notochord and somite by Kirby and Gilmore [1972], Strudel et al [1977], Lauder et al [1980], Newgreen et al [1981], and Wallace [1982]. Our current observations thus confirm their data.…”
Section: Net Immunoreactivity In the E35 Quail Embryosupporting
confidence: 92%
“…This hypothesis is supported by previous work on sea urchins (21,39), where 5-HT was found to be an important stimulus for epithelial-mesenchymal transformation during gastrulation. Similarly, Wallace (29) demonstrated the transient ability of the floor plate of the neural tube to take up 5-HT synthesized by the notochord in stage 10-12 chick embryos. This ability is expressed not only at the rostral end of the neural tube but also at the caudal end, where gastrulation is still ongoing in association with the persistent primitive streak.…”
Section: Discussionmentioning
confidence: 94%
“…In the developing heart, Yavarone et al (25) Evidence that 5-HT regulates craniofacial and cardiac development is consistent with studies by Buznikov and colleagues (26,27) using the sea urchin embryo, indicating that either 5-HT or a 5-HT-like substance is involved in early morphogenetic events, such as cleavage and gastrulation, prior to formation of the nervous system. Likewise, 5-HT has been implicated in gastrulation and neurulation during early avian development (28)(29)(30). The presence of 5-HT during gastrulation is particularly interesting with respect to NC cell migration, since both processes have been suggested to be pivotal for determination of the body plan (8), and in each case, an ectodermal layer undergoes transformation into a mesenchyme and then proceeds to migrate away from its site of origin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wallace (20) found that the embryo produces serotonin as early as stage 10. In addition, egg yolk contains epinephrine and norepinephrine (21).…”
Section: Discussionmentioning
confidence: 99%